2008
DOI: 10.1177/1010539508322762
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anemia and Its Determinants Among Nonpregnant and Pregnant Women in India

Abstract: This study investigates the severity and distribution of anemia among nonpregnant and pregnant women aged 15 to 49 years in urban and rural sectors of 26 states in India and its association with certain economic and biosocial factors. A national survey was conducted to collect data on hemoglobin, height, weight, and certain economic and biosocial factors of 72 660 nonpregnant and 5619 pregnant women. Nonpregnant women aged less than 25 years are most affected by anemia. Women's education and standard of living… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
54
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 19 publications
11
54
3
1
Order By: Relevance
“…[15][16][17][18][19][20] Understanding the social patterning of anaemia and heterogeneity among different groups and across states, and exploring the changing patterns of anaemia distribution over time may help elucidate which factors drive these changes, and identify interventions to address this significant health burden.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…[15][16][17][18][19][20] Understanding the social patterning of anaemia and heterogeneity among different groups and across states, and exploring the changing patterns of anaemia distribution over time may help elucidate which factors drive these changes, and identify interventions to address this significant health burden.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Singh MB et al 15 in Rajasthan, India, reported similar findings i.e., prevalence among pregnant and lactating women was more as compared to non-pregnant/non-lactating. Other studies in India 5,12,13,17,23,26,32,33 also reported high prevalence of nutritional anaemia among pregnant and lactating females.…”
Section: Discussionmentioning
confidence: 98%
“…When examining other factors possibly influencing the development of anemia in pregnancy, published reports have indicated that conditions such as the women's age, 19 education status, 20 nutritional habits, [6] smoking status [21], gravidity [22], parity [23], and the interval between consecutive pregnancies [24] may play a role.…”
Section: Discussionmentioning
confidence: 99%